The Erdogan Experiment in Turkey Is the Future - Graham E. Fuller (International Institute of Islamic Thought, 2005)
Response to Ariel Cohen: In his answer to question 1, Ariel Cohen offers a pretty good definition of a moderate Muslim, one that I can subscribe to as far as it goes. The problem comes more with his definition of radical. If all armed resistance to foreign occupation is to be condemned – which over the course of history has widespread acceptance as a legitimate action – then of course large numbers of Muslim activists fall into the category of radical. Surely Cohen would not wish to suggest that those guerrilla activities that have led to the founding of such countries as the United States, Israel, Kenya, South Africa, and Algeria via anti-colonial struggles are all unacceptable because they passed through a certain violent phase – including elements of what might be terror. I agree with him, as do most Muslims, that in principle, killing innocent civilians constitutes an act of terrorism. But that holds true whether it takes place from suicide bombers at a distance of five feet or from 5,000 feet when “legitimate government” bombs are dropped on resistance forces and surrounding civilians. Sadly, much of this debate these days really comes down to the specific tragic events currently unfolding in Israel and Palestine, in which each side seeks the moral high ground for its own version of the issue. If either the Israelis or the Palestinians seek an exclusive monopoly on that moral high ground, then we will lose all moral clarity and will simply be engaged in propaganda exchanges. The reality is that the current American dragnet of anti-terrorism, as well as that of many other countries, sweeps excessively wide in quickly marking individuals as “radical,” and hence “dangerous” or “linked to terrorism.” Here in this forum, we cannot just sift the ideological purity of our favorite radicals or moderates. I would only suggest that if we define politically active Islamists like Tariq Ramadan as “dangerous” and beyond the pale of acceptance for dialogue, then we are indeed defining ourselves out of any serious dialogue with important and influential Islamist leadership. Such narrowness of vision coupled with a lack of respect for human rights in the investigation of Muslims is what has created the widespread impression that the United States is engaged in a “war against Islam.” We cannot afford to leave that impression ...